Kinerja Proyek terhadap Efisiensi Waktu dan Biaya dalam Proyek Percepatan Konstruksi Pembangunan Gedung Kantor Kejaksaan Negeri Tual - Iren Sabina Lestia; Lenora Leuhery; Henriette Dorothy Titaley; M. Alit Suryawan (Universitas Batanghari Jambi, 2026)
Public construction projects frequently encounter challenges related to schedule delays and cost overruns, which can reduce overall project performance. These conditions require an integrated project control system to ensure that implementation remains aligned with planned schedules and budgets. One approach that can be applied is Earned Value Management (EVM), a performance evaluation method that integrates cost and schedule analysis simultaneously, enabling early detection of project deviations. This study aims to evaluate time and cost performance in the Acceleration Project of the Tual District Attorney Office Building Construction and to assess the effectiveness of the acceleration strategy implemented during project execution. The research method uses secondary data analysis consisting of the Bill of Quantities (BOQ), S-curve, weekly progress reports, and actual cost data. These data are analyzed using Planned Value (PV), Earned Value (EV), Actual Cost (AC), and performance indicators including the Cost Performance Index (CPI), Schedule Performance Index (SPI), and Critical Ratio (CR). The results indicate that the project was completed in 26 weeks compared to the planned 33 weeks, resulting in a time efficiency of 7 weeks with an SPI value greater than 1. Although cost inefficiency occurred during the early stages of implementation (CPI < 1), effective cost control measures successfully stabilized expenditures by the end of the project, resulting in CPI and CR values reaching 1. Based on these findings, the application of EVM is recommended as a routine monitoring method for accelerated construction projects to ensure more accurate, systematic, and data-driven control of project time and costs.